Thermal influence on the electrochemical behavior of a supercapacitor containing an ionic liquid electrolyte. (10th February 2018) - Haque, Mazharul; Li, Qi; Smith, Anderson D.; Kuzmenko, Volodymyr; Köhler, Elof; Lundgren, Per; Enoksson, Peter
Abstract: Emerging demands on heat-durable electronics have accelerated the need for high temperature supercapacitors as well as for understanding the influence of elevated temperatures on the capacitive behavior. In this work, we present a comprehensive study of the thermal influence on a supercapacitor containing 1-ethyl-3-methylimidazolium acetate (EMIM Ac) electrolyte and activated carbon (AC) electrodes. The performance variation as a function of temperature in a range from 21 °C to 150 °C reveals that a high specific capacitance of 142 F g −1 can be achieved at 150 °C at a current density of 2 A g −1 with a rate capability of 87% at 15 A g −1 (relative to 2 A g −1 ). At 150 °C, equivalent series resistance (ESR) is only 0.37 Ω cm 2, which is a result of improved ionic conductivity of the electrolyte at elevated temperature. The ESR value of 2.5 Ω cm 2 at room temperature reflects a good compatibility between EMIM Ac and AC. In addition, a capacitance retention of more than 95% (in the end of 1000 cycles) is maintained up to 120 °C followed by 85% at 150 °C. These results confirm EMIM Ac as a suitable candidate for carbon-based high temperature supercapacitors, and the observations regarding the thermal influence on performance metrics e.g. usable operation voltage could be applicable to other energy storage devices. Highlights: Ionic liquid EMIM Ac is used as an electrolyte for a carbon-based supercapacitor. Good affinity between AC and EMIM Ac is revealed by low interfacial resistance. An improved capacitive performance is observed with elevated temperature. Acceptable performance is maintained up to 150 °C. IR drop decreases significantly at high temperature operation.